Find the least integral value of f ( x ) = ( x − 1 ) 5 ( x − 1 ) 7 + 3 . ( x − 1 ) 6 + ( x − 1 ) 5 + 1 , ∀ x > 1
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can simplify it to ( x − 1 ) 2 + 3 ( x − 1 ) + 1 + ( x − 1 ) 5 1 which is ( x − 1 ) 2 + ( x − 1 ) + ( x − 1 ) + ( x − 1 ) + 1 + ( x − 1 ) 5 1 Now, since (x-1)>0 , therefor we can apply the AM -GM>0 inequality , which gives ( x − 1 ) 2 + ( x − 1 ) + ( x − 1 ) + ( x − 1 ) + 1 + ( x − 1 ) 5 1 ≥ 6 × 1 Thus the least integral value is 6
Problem Loading...
Note Loading...
Set Loading...
First of all to simplify the expansion replace x − 1 by t so that t > 0 ∀ x > 0 . f ( t + 1 ) = t 2 + 3 t + t + t 1 5 We see that the given function is integer only for t = 1 . Hence we substitute t = 1 and we get:- f ( 2 ) = 1 + 3 + 1 + 1 f ( 2 ) = 6 f ( 2 ) = 6 is the only integral solution.